(DIS)INFORMATION IN TWITTER ECHO CHAMBERS: disputes over chloroquine during the Covid-19 pandemic - Lima, Cecília Almeida Rodrigues (2020)
In view of the large flow of information circulating on Twitter regarding the Covid-19 pandemic, this paper analyzes the polarization of the debate around the effectiveness of the use of chloroquine and hydroxychloroquine in the treatment of the disease, based on different reference systems, in addition to identifying the signs of disinformation present in the links that most circulated between March 23 and April 13, based on a base of 21,076 tweets. The analysis finds the formation of echo chambers, in a clear opposition between the use of traditional communication vehicles and sites of explicitly ideological content as sources of reference to defend a drug without proven scientific efficacy.